Effects of 3-year cultivation on the soil nutrient status in a tropical forest and savanna of Central Africa, as determined by the microbial responses to substrate addition. Issue 6 (2nd November 2018) - Sugihara, Soh; Fujimori, Yoko; Shibata, Makoto; Sawada, Kozue; Tanaka, Haruo; Mvondo Ze, Antoine D.; Araki, Shigeru; Kosaki, Takashi; Funakawa, Shinya
ABSTRACT: The forest–savanna transition zone is widely distributed on nutrient-poor Oxisols in Central Africa, and a population explosion has led to the rapid cultivation of these vegetation types in this zone. To reveal and compare the effects of short-term (3 years) cultivation on the soil nutrient status of the forest and savanna vegetation in this area, we evaluated microbial nutrient limitation and availability by conducting hourly measurements of soil microbial respiration after the addition of glucose in combination with nitrogen (N) and/or phosphorus (P) to soils that were collected from a forest site (FOR), a savanna site (SAV), as well as cropland for 3 years derived from a forest (Crop-F) and a savanna (Crop-S), in eastern Cameroon. The N addition had little effect on the pattern of microbial respiration rate for the FOR and Crop-F sites, indicating N rich for microbes. In contrast, N addition resulted in the increases in maximal respiration rates after the exponential increase for the SAV and Crop-S sites, indicating microbial N limitation, and cultivation accelerated the soil N depletion. Furthermore, we observed that P addition resulted in the increase in the maximal respiration rates, indicating microbial P limitation for all sites, except for FOR site. Since the cultivation significantly affected the microbial properties only in the forest ecosystem, such as the increase in the microbial specific growth rate and the decreased microbial C:N and C:P ratios, these changes would induce the P limitation for Crop-F. These results indicate that (1) the FOR site was a N-rich ecosystem for soil microbes, and 3 years of cultivation in the Crop-F site did not alter the high soil N status but induced microbial P limitation, with the changes in the microbial properties, and that (2) the SAV site was N and P limited for soil microbes, and 3 years of cultivation clearly decreased the soil N availability.